2018
DOI: 10.1155/2018/3801479
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Antibiogram of Bacteria Isolated from Milk of Goats with Subclinical Mastitis in Thika East Subcounty, Kenya

Abstract: A cross-sectional study was carried out to determine the prevalence and risk factors of subclinical mastitis in dairy goats in Thika East Subcounty, Kenya. Further the bacterial pathogens and their antibiogram were investigated. Farm level data on risk factors were obtained from 41 farmers using questionnaires. Milk was obtained from 110 lactating dairy goats and tested for submastitis using California Mastitis Test (CMT). The prevalence of subclinical mastitis at goat level was estimated to be at 50.9% using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
45
4
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 34 publications
9
45
4
6
Order By: Relevance
“…The susceptibility of the isolates to ampicillin was within the range reported by Widianingrum et al in 2016. The resistance observed for ampicillin (100%) is also in agreement with the reports by Mahlangu et al (2018) who observed a resistivity of 100% to ampilcillin in a study carried out in Zaria. The resistance (40.63%) of the isolates to tetracycline in this study may reflect the excessive use of the drug in treatment in the study area.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The susceptibility of the isolates to ampicillin was within the range reported by Widianingrum et al in 2016. The resistance observed for ampicillin (100%) is also in agreement with the reports by Mahlangu et al (2018) who observed a resistivity of 100% to ampilcillin in a study carried out in Zaria. The resistance (40.63%) of the isolates to tetracycline in this study may reflect the excessive use of the drug in treatment in the study area.…”
Section: Resultssupporting
confidence: 91%
“…The increase in prevalence of mastitis with age may be due to the fact that older goats are long term nannies that have stayed longer in the herd and hence are at higher risk of coming into contact with mastitis causing organisms than the younger does. Old age and multiple parturitions have been reported to produce stress on animals and as a result, such animals become susceptible to infectious agents due to low immunity level (Mahlangu et al, 2018). The result of this study differs from the findings of the study of Mahlangu et al (2018) who reported that goats of age 1year had a prevalence of SCM of 67% as compared to older goats of 2 and 3 years which had a prevalence of 46% and 50% respectively.…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations